Association of nailfold capillaroscopic findings with clinical features in patients with systemic sclerosis - Tajkia Haque; Md. Abu Shahin; Md. Ariful Islam; Iftekhar Hussain Bandhan; Minhaj Rahim Choudhury; Syed Atiqul Haq; Mohammad Mostafa Zaman (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Microvascular damage is one of the most important etiopathogenetic and clinical characteristics of systemic sclerosis (SSc). Nailfold capillaroscopy (NFC) is a simple, non-invasive, and inexpensive imaging technique to assess the skin microcirculation. The aim of this study was to determine the association between NFC findings and clinical features in patients with SSc.